AB0518 Synovial biomarkers in peripheral spondyloarthritis. (23rd January 2014) - Cozzi, L.; Felicetti, M.; Oliviero, F.; Sfriso, P.; Lunardi, F.; Calabrese, F.; Vezzù, M.; Costa, L.; Caso, F.; Stramare, R.; Rubaltelli, L.; Dayer, J. M.; et al.
Abstract : Objectives: To analyse a panel of synovial fluid (SF) and synovial tissue (ST) biological markers expression at single joint level to find candidate biomarkers in resistant peripheral spondyloarthritis (SpA). Methods: Twenty seven resistant SpA patients with knee joint synovitis, included in an Intra-articular (IA) TNF alpha blocking open-label study 1, were treated with biweekly four IA Etanercept injections (12.5 mg) in a single knee joint. The primary outcome (Thompson's knee index: THOMP) and secondary outcomes were assessed at baseline and at week 8 of the study. The secondary outcomes are: C-reactive protein; Knee Joint Articular Index (KJAI), Health Assessment Questionnaire disability index (HAQ-DI), maximal synovial thickness by gray-scale ultrasonography (US-MST), synovial tissue cluster differentiation CD45+ mononuclear cell (ST-CD45+), synovial tissue-CD31+ vessels (ST-CD31+), and along with levels of synovial fluid (SF) soluble inflammation makers such as Interleukin 1ß (SF-IL 1ß), Interleukin 1 Receptor antagonist (SF-IL 1Ra) and Interleukin 6 (SF-IL 6). Results: At the end of the study, composite clinical indexes, US-MST, ST and SF biological markers were significantly reduced compared to baseline. There was a significant correlation between CRP and THOMP, or KJAI, or HAQ-DI, or SF-IL 1Ra; between KJAI and THOMP or US-MST; between ST-CD45+ and THOMP, or KJAI or ST-CD31+, or SF-IL 1ß; between SF-IL 6 and THOMP, or KJAI, or SF-IL 1ß, or SF-IL 1Ra; between SF-IL 1 Ra and SF-IL 1ß. Comparing pre- versus post-IA Etanercept injection changes (Δ), we found a significant correlation between ΔCRP with ΔSF-IL 1ß, ΔKJAI with ΔTHOMP and ΔSF-IL 6; Δ HAQ with ΔSF-IL 6; ΔST-CD-45+ with ΔSF-IL 1ß; ΔSF-IL 6 and ΔSF-IL 1ß; ΔSF-IL 1Ra with ΔSF-IL 1ß and ΔSF-IL 6. Conclusions: The significant association at single joint level of composite clinical indexes to inflammatory soluble markers and to synovial tissue marker expression, as well as between clinical and synovial biomarkers changes following IA-anti TNF-alpha blockers treatment, suggest that CD45+ in synovial tissue and IL-6 and IL-1β in SF may be considered potential biomarkers of the peripheral SpA response to IA TNF- alpha blocking. References: Fiocco U. et al: Synovial Biomarkers in Psoriatic Arthritis. J Rheumatol Suppl. 2012 Jul;89:61-4. doi: 10.3899/jrheum.120246 Disclosure of Interest: None Declared